Survival benefit of chemotherapy in a contemporary cohort of metastatic urachal carcinoma - Flammia, Rocco Simone; Chierigo, Francesco; Würnschimmel, Christoph; Horlemann, Benedikt; Hoeh, Benedikt; Sorce, Gabriele; Tian, Zhen; Leonardo, Costantino; Tilki, Derya; Terrone, Carlo; Saad, Fred; Shariat, Shahrokh F; et al. (Urologic oncology, 2022)
BACKGROUND: We relied on the most contemporary Surveillance, Epidemiology, and End Results (SEER) database and tested the hypothesis that chemotherapy may improve survival in metastatic urachal carcinoma (m-UraC). MATERIAL AND METHODS: Within the SEER database (2004-2016), we identified m-UraC patients aged ≥ 18 years. Propensity score matching (PSM: cystectomy status, age and sex), Kaplan-Meier plots, cumulative incidence plots, Cox regression models and competing risks regression (CRR) models addressed overall mortality (OM) and cancer-specific mortality (CSM). RESULTS: Overall, 274 m-UraC patients were identified with a median age of 70 years. Most were male (66%) and Caucasian (72%). Overall, 32% received chemotherapy. Chemotherapy-exposed patients were younger (62 vs. 73 years, p<0.001) and more frequently underwent cystectomy (19 vs. 8%, P = 0.014). In 274 m-UraC patients, median OM and CSM were 6 (4 -10) months and 8 (6 -14) months, respectively. After 1:1 PSM, chemotherapy-exposed patients exhibited lower OM (median 16 vs. 3 months; multivariable HR 0.38, P <0.001) and lower CSM (median 17 vs. 4 months; multivariable CRR HR 0.52, P = 0.001). The association between chemotherapy and better survival was even stronger in younger (≤70 years) patients (OM HR: 0.23, P <0.001; CSM CRR HR: 0.42, P = 0.001), but not in older (≥71 years) patients (OM HR: 0.61, P = 0.2; CSM CRR HR: 1.02, P = 1), after PSM and multivariable adjustments. CONCLUSION: Overall, we validated the very aggressive nature of UraC, when distant metastases are present, and observed that m-UraC patients exposed to chemotherapy exhibited lower OM and CSM.
Keywords: nádory močového měchýře; SEER Program; Cystectomy; program SEER; Male; cystektomie; Aged; lidé; Female; mužské pohlaví; ženské pohlaví; senioři; Urinary Bladder Neoplasms; Humans; karcinom z přechodných buněk; Carcinoma, Transitional Cell